A new audio augmented reality interaction and adaptation model for museum visits. (June 2020) - Kaghat, Fatima Zahra; Azough, Ahmed; Fakhour, Mohammed; Meknassi, Mohammed
Abstract: Augmented Reality is a recent impressive technology applied in many areas. However, in tourism and especially in museums, where visual contact with exhibitions is fundamental, augmenting reality with graphical objects, or using graphical applications, can distract visitors' attention from the main subject. Also, having a classical experience with no personalization or adaptation can make a negative sensation for the whole experience. In this paper, we introduce an adaptive gesture-based audio augmented reality system, in which content personalization is a key design for the interaction experience. The evaluation has been conducted in a real environment which was the Musée des arts et Métiers in Paris. This evaluation has confirmed the ease of use, as well as the usefulness and enjoyment impact of our model.